Noradrenaline enhances angiotensin II responses via p38 MAPK activation after hypoxia/re-oxygenation in renal interlobar arteries - Kaufmann, Jana; Zavaritskaya, Olga (Acta physiologica, 2015)
Aim: Hypoxia and sympathetic activation are main factors in the pathogenesis of acute kidney injury (AKI). We tested the hypothesis that noradrenaline (NE) in combination with hypoxia aggravates the vasoreactivity of renal arteries after hypoxia/re-oxygenation (H/R). We tested the role of adrenergic receptors and p38 MAPK using an in vitro H/R protocol. Methods: Mouse interlobar arteries (ILA) and afferent arterioles (AA) were investigated under isometric and isotonic conditions respectively. The in vitro protocol consisted of 60-min hypoxia and control condition, respectively, 10-min re-oxygenation followed by concentration-response curves for Ang II or endothelin. Results: Hypoxia reduced the response to Ang II. Hypoxia and NE (10−9 mol L-1) together increased it in ILA and AA. In ILA, NE alone influenced neither Ang II responses under control conditions nor endothelin responses after hypoxia. Prazosin or yohimbine treatment did not significantly influence the NE+hypoxia effect. The combination of prazosin and yohimbine or propranolol alone inhibited the effect of NE+hypoxia. BRL37344 (β3 receptor agonist) mimicked the NE effect. In contrast, the incubation with β3 receptor blocker did not influence the mentioned effect. Phosphorylation of p38 MAPK and MLC(20) was increased after H/R with NE and Ang II treatment. The selective p38 MAPK inhibitor SB202190 blocked the NE+hypoxia effect on the Ang II response. Conclusion: The results suggest an interaction of NE and hypoxia in enhancing vasoreactivity, which may be important for the pathogenesis of AKI. The effect of NE+hypoxia in ILA is mediated by several adrenergic receptors and requires the p38 MAPK activation.